Essential questions in EU law - Reinisch, August 1965- (Cambridge University Press, 2009)
To the new student of EU law, deciding what questions to ask on the subject is as much of a challenge as answering them. This introduction's distinctive Q & A format immediately directs the student to the questions he or she should be asking. Concise and clearly structured, it guides students through the different layers of the European Union from the law establishing it, through how its institutions work and on to its operation on the international stage. It also provides a clear explanation of the substantive law of the EU and the working of the internal market. Each chapter takes a cornerstone of EU law, sets the scene with a short introductory overview and then tackles its key questions. Providing enough detail to give a solid foundation to this complex subject without losing the student with excessive detail, it is an essential first port-of-call for study in the subject
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Europäische Union; Recht; Law / European Union countries / Miscellanea; Europäische Union. Mitgliedsstaaten; Einführung